Rectifying the identities of the males of two Micrathena species (Araneae: Araneidae), with report of the first case of intersexuality in the genus - de Alvarenga, Alessandra Da Silva; Magalhaes, Ivan L. F.; Da Fonseca, Rodrigo Nunes; Pérez-González, Abel (Zootaxa, 2020)
Despite extensive taxonomic work on the Neotropical fauna of the spider genus Micrathena Sundevall, for 27 out of 117 (23%) species only the female morphology has been described, and some of the previously hypothesized male-female matches have been proven erroneous. This work provides new insight about sex matching in two species: Micrathena ruschii (Mello-Leitão, 1945) and Micrathena lata Chickering, 1960. For Micrathena ruschii, the male previously hypothesized to belong to this species was collected with females in Itatiaia; we here present morphologically different males, also collected with females, in Macaé, both in Rio de Janeiro, Brazil. Through a DNA barcoding approach, we present molecular evidence indicating conspecificity of M. ruschii females with the males collected in Macaé, proving the male from Itatiaia to be a misidentification. Therefore, a description of the correct male of Micrathena ruschii is herein provided. The male previously identified as M. ruschii probably represents an undescribed species but is not named here due to scarcity of material. We also describe for the first time the male of Micrathena lata based on one specimen collected in Misiones, Argentina. This male specimen belongs to the militaris species group, where M. lata is the only species from the Atlantic Forest previously only known by females. In addition, we detect an intersexual specimen of Micrathena ruschii, revealing the first case of intersexuality for the genus.